KEDUDUKAN PERJANJIAN DAN ETIKA BAIK DALAM SENGKETA PENGALIHAN SEWA MENYEWA MOBIL KEPADA PIHAK KETIGA - Mahardika, Gagah; Untoro (Jurnal De Jure Muhammadiyah Cirebon, 2025)
A repeat rental agreement in a car rental agreement is basically permissible if it has been clearly agreed upon beforehand. However, repeat car rentals carried out by renters without permission also often occur. The problem that arises from this lease repeat agreement is that there is often a dispute over the responsibilities of the parties if other damage/loss occurs. However, in reality, sometimes individuals rent out cars to other parties with the aim of making a profit from the car rental proceeds without the knowledge of the car owner and returning the car in a damaged condition. Keywords: Agrement; Four Wheel Vehicle; Leas.